Theoretical foundations of studying phraseological units denoting time in English and Uzbek - Sultonova, Navro‘za Ikromali kizi; Azizova, Fotimakhon Saidbakhromovna (The Lingua Spectrum, 2026)
This article explores the theoretical foundations of studying phraseological units that denote, conceptualize, and culturally interpret the concept of time in English and Uzbek languages. Phraseological units are examined not merely as fixed lexical combinations, but as linguocultural signs that encode collective experience, national mentality, axiological values, metaphorical thinking, and communicative norms of different speech communities. The research emphasizes that the concept of time in phraseology is multidimensional, reflecting both universal cognitive patterns and culture-specific interpretations. In English and Uzbek, temporal phraseological units express various semantic aspects such as duration, immediacy, delay, opportunity, patience, life stages, and social expectations. The study also highlights the importance of cognitive semantics and linguocultural approaches in revealing how abstract temporal concepts are structured through metaphorical and figurative language. A comparative analysis of English and Uzbek phraseological systems demonstrates both similarities rooted in shared human cognition and differences shaped by distinct cultural worldviews. The findings show that time in phraseology functions not only as a chronological measure but also as a cultural, moral, and psychological construct that reflects how societies perceive life, behavior, and human experience.